University adult education approches: developing a model for the Qwa-qwa campus of the University of the North - Matobako, Thabang Sello (My University, 2014)
This study develops a model for university adult education to guide the Qwa-Qwa Campus of the University of the North in its quest to play a role in adult education practice. It explores the route that the Qwa-Qwa Campus could take in extending its resources to a wide range of individuals, special interest groups and targeted audiences in the North-Eastern Free State community that was historically marginalised from university education. In developing the envisaged model the study explores a number of international and local (South African) approaches in university adult education. This academic endeavour is intended to provide some guidelines for the Qwa-Qwa Campus’ envisaged role in university adult education. In pursuance of these aims (lie study investigates the typical role that a university plays in adult education by reflecting on the following issues: _ University outreach __ Distance education _ University Extension programmes / service _ University adult and ccntmuing education _ Universities and communities __ Sources o f funding for university adult education practice. A review of literature including a home-page survey are used as methodologies of unravelling typical University Adult Education approaches of four universities in Australia ii(La Trobe, Deakin, Ballarat and Charles'STtirt), one university in the United States of America (Tuskegee), two universities in Southe; s Africa (Botswana and Lesotho) and four Universities in South , . . Africa (Western Cape, Cape ToWd, Witwatersrand and Transkei). Key people at selected South African Universities actively involved in adult education practice were interviewed. Three people fi/nn the community were interviewed to assess the needs of surrounding people in the Qwa-Qwa area. The study brings these elements together in an attempt to develop a realistic model for the involvement of the Qwa-Qwa Campus in adult education.
Keywords: Continuing education--South Africa; Distance education--South Africa; University extension--South Africa; Adult education--South Africa; University of the North (South Africa)